TRYPOD POSITION AND PURSED LIP BREATHING TOWARDS IMPROVING OXYGEN SATURATION - Ulfah, Maria; Septiany, Maulidya; Aridamayanti, Bernadetta Germia (Program Studi Keperawatan Universitas Jambi, 2026)
Background: Pleural effusion involves abnormal fluid accumulation in the pleural cavity, stemming from increased production or reduced lymphatic absorption. This buildup compresses the lungs, impairing expansion and causing symptoms like dyspnea, chest pain, and cough. Non-pharmacological interventions, such as the tripod position and pursed-lip breathing, enhance lung ventilation, oxygenation, and ease breathing effort. Objective: This case report evaluates their application in nursing care for Mrs. S, a patient with pleural effusion, to boost oxygen saturation. Methods: A descriptive case study design targeted one patient diagnosed with pleural effusion. Data were gathered via medical-surgical nursing assessments, including interviews, observations, and physical exams. Findings informed a tailored nursing care plan. Interventions comprised tripod positioning where the patient leans forward with arms supported on a surface to optimize the use of diaphragmatic breathing along with pursed-lip breathing, involving inhalation through the nose and prolonged exhalation through pursed lips to reduce air trapping and improve gas exchange. These were implemented daily for three consecutive days, with ongoing monitoring and evaluation of vital signs, particularly SpO2. Result: Pre-intervention, Mrs. S exhibited SpO2 of 84%, marked dyspnea, and ineffective airway clearance. Post-intervention, SpO2 rose to 96%, with notable relief in shortness of breath and enhanced respiratory comfort. No adverse effects occurred, confirming intervention tolerability. Conclusion: The use of the tripod position and pursed lip breathing technique has been shown to improve oxygen saturation in Mrs. S with a nursing diagnosis of impaired gas exchange. Keywords: Pleural Efussion, Tripod Position, Pursed Lip Breathing